SOCIAL AND CULTURAL LIFE OF NIZAMI ARUZIY SAMARQANDI AND HIS TIME (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
Today, the issue of raising society to spiritual heights has also become one of the most important components of the policy of the Republic of Uzbekistan. A new, unbiased and pure scientific attitude to our heritage in the ancient moral and educational spirit on the basis of the ideology of national independence presupposes scientific-theoretical, scientific-methodological research in New Directions in this area as well. With this goal, this article will focus on the work of Nizami Aruziy Samarqandi and the social cultural life of that time. In the development of Adib's work, as far as possible, the views on such issues as the role of Nizami Samarkandi are expressed. The article also aims to define the literary environment in which the poet lived and worked, their importance in the work of adib and their place in the development of Oriental literary studies.